"It's Pretty Futurey": Retrofuturism and Anachronism in Loki. - SHAW, CAITLIN (Clio (0884-2043))
The article "It's Pretty Futurey": Retrofuturism and Anachronism in Loki" analyzes the Marvel TV series Loki, focusing on the character's interactions with the Time Variance Authority (TVA) and how the show challenges normative timelines and power structures through diverse historical settings and anachronism. By critiquing the TVA's enforcement of an official historical narrative, the show invites contemplation of social critique and celebrates diversity and autonomy. Through its use of historical authenticity and anachronism, Loki offers a subversive narrative that challenges oppressive social orders and promotes inclusivity. The text also examines how science fiction in American television has historically addressed social issues and how mainstream media's use of historical bricolage challenges traditional narratives and exposes hegemonic processes.